2018
DOI: 10.1080/02713683.2018.1478981
|View full text |Cite
|
Sign up to set email alerts
|

Biometric Factors Associated with the Visual Performance of a High Addition Multifocal Intraocular Lens

Abstract: The visual performance at near distance with the IOL evaluated improved in eyes with less corneal power. On the other hand, a slight temporal IOL decentration from vertex normal also improved intermediate visual acuity. The binocular defocus curve was similar to other trifocal IOLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 35 publications
(40 reference statements)
7
31
3
Order By: Relevance
“…The defocus curves of the add-on lens were found to be similar to those of the Liberty trifocal capsular bag IOL made by the same manufacturer. [16][17][18] In this study, we also compared the defocus curves of the supplementary IOL to a subset of patients previously implanted with a primary capsular bag trifocal IOL, which is considered the "gold standard" for trifocal lenses. We found that the add-on lens provided better visual acuities in the intermediate (−1.5 to −2.0 D) and near (−3.5 D and −4.0 D addition) ranges of vision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The defocus curves of the add-on lens were found to be similar to those of the Liberty trifocal capsular bag IOL made by the same manufacturer. [16][17][18] In this study, we also compared the defocus curves of the supplementary IOL to a subset of patients previously implanted with a primary capsular bag trifocal IOL, which is considered the "gold standard" for trifocal lenses. We found that the add-on lens provided better visual acuities in the intermediate (−1.5 to −2.0 D) and near (−3.5 D and −4.0 D addition) ranges of vision.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,14,15 According to the manufacturer, the 1stQ AddOn diffractive supplementary IOL has an optic similar to the Medicontur Liberty ® 677MY capsular bag IOL, with clinical trifocal performance and spectacle independence of patients being confirmed in related studies. [16][17][18]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, new metrics can be derived in real time such as the area under the defocus curve, which so far was only possible with complex analysis difficult to implement for the clinician [32]. This new metric can help to predict the visual performance before surgery based on biometric eye characteristics as we have recently demonstrated [35].…”
Section: Discussionmentioning
confidence: 99%
“…Some retrospective data and biometric eye parameters described in Table 1 were also obtained for the eye randomly selected with the Pentacam AXL (Oculus Optikgeräte, Wetzlar, Germany), IOL Master 500 (Carl Zeiss Meditec AG, Jena, Germany), and Keratograph 5M systems (Oculus Optikgeräte, Wetzlar, Germany). The same iPad was used to measure the contrast sensitivity defocus curve (CSDC) with a Multifocal Lens Analyzer (3.0; Snellen letters; https://www.defocuscurve.com/en/; Accessed 5 May 2021) [19,20]. Defocus lenses from +1.00 D to −4.00 D, in steps of +0.50 D, were selected for measuring CSDC at 4 m in the randomly selected eye, with a best distance spectacle refraction and vergence distance correction of +0.25 D. The Light Distortion Analyzer (CEORLab, University of Minho, Braga, Portugal) was used to measure the photic phenomena monocularly, with the best distance correction in the eye randomly selected and binocularly without correction 2 m from the observer (proximal vergence corrected with +0.50 D).…”
Section: Clinical Proceduresmentioning
confidence: 99%